Factors influencing quality of work life (qwl) for employees at Syauqi Group, Shah Alam, Selangor Darul Ehsan / Rabeiatul Adawiah Nordin - Nordin, Rabeiatul Adawiah (Faculty of Business and Management, 2017)
The study aims to identify factors influencing quality of work life at Syauqi Group, Shah Alam, Selangor. The objectives of this study were to examine the association between independent variables (work life balance, communication, teamwork and empowerment) and dependent variable (quality of work life) among employees at Syauqi Group, Shah Alam, Selangor. Moreover, this study employed descriptive study. Meanwhile, the primary data was collected through questionnaires with 50 respondents were selected. Eventually, the findings of this research show only two variables (work life balance and empowerment) were significant with dependent variable (quality of work life). The communication and teamwork has shown not significant. Next, the most significant variable of quality of work life was work life balance. Thus, this study has recommended that to increase level of work life balance in the organization to ensure that the employee can balance their time with working and other nonworking activities. Other than that, the employees should improve their level of empowerment and understanding with other employees and also their task. It will make the work can be more easy to do if they work and discuss together.